Liver resection with thrombectomy for patients with hepatocellular carcinoma and tumour thrombus in the inferior vena cava or right atrium. Issue 2 (3rd February 2020) - Matsukuma, S; Eguchi, H; Wada, H; Noda, T; Shindo, Y; Tokumitsu, Y; Matsui, H; Takahashi, H; Kobayashi, S; Nagano, H
Abstract: Background: Hepatocellular carcinoma (HCC) with tumour thrombus (TT) in the inferior vena cava (IVC) or right atrium (RA) is a rare advanced disease state with a poor prognosis. The aim of this study was to examine survival after surgical resection. Methods: Patients with HCC and TT of either the IVC or RA, who underwent liver resection between February 1997 and July 2017, were included. Their short- and long-term outcomes and surgical details were analysed retrospectively. Results: Thirty-seven patients were included; 16 patients had TT in the IVC below the diaphragm, eight had TT in the IVC above the diaphragm, and 13 had TT entering the RA. Twelve patients had advanced portal vein TT (portal vein invasion (Vp) greater than Vp3 and Vp4), ten had bilobar disease, and 12 had extrahepatic disease. There were no in-hospital deaths, although two patients died within 90 days. Median survival did not differ between patients who had resection with curative intent (18·7 months) and those with residual tumour in the lung only (20·7 months), but survival was poor for patients with residual tumour in the liver (8·3 months). Conclusion: Liver resection with thrombectomy for advanced HCC with TT in the IVC or RA is safe and feasible, leading to moderate survival. Graphical Abstract: Hepatocellular carcinoma with tumour thrombus in the inferior vena cava or right atrium is an advanced disease state with a poor prognosis. This retrospective study examined the survival benefits of surgical resection for patients with this rare condition. Liver resection with thrombectomy in these patients was safe and feasible, especially for those who had a curative resection or residual tumour in the lung only. Liver resection for HCC with caval thrombi is feasible with moderate survival